Short-fiber carbon-ceramic composite material brake disc and preparation method thereof

Through the combination of modified chopped carbon fiber and other raw materials and the temperature-pressure forming-sintering process, the problems of long manufacturing cycle and high cost of carbon ceramic brake discs are solved, and its high temperature resistance, thermal shock resistance and wear resistance are improved, and the performance of high temperature resistance is extended. Service life.

CN119191865AInactive Publication Date: 2024-12-27SHANDONG JINGCHENG NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411325613.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing carbon ceramic brake disc has a long manufacturing cycle and high cost, resulting in insufficient performance, poor high temperature resistance and thermal shock resistance, which restricts the improvement of its service life.

Method used

The preparation method of the brake disc using the short fiber carbon ceramic composite material includes modified chopped carbon fiber, boron carbide, binder, kaolin, boron nitride, aluminum nitride, carbon black, graphite, modified dispersants and other raw materials, through Preparation is carried out by mixing, pretreatment, temperature pressing molding, glue discharge, sintering and finishing steps to optimize the performance of carbon ceramic composite materials.

Benefits of technology

It shortens the manufacturing cycle, reduces production costs, improves the high temperature and thermal shock resistance of carbon ceramic brake discs, and improves its wear resistance consistency and service life, achieving more efficient production and performance improvement.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a short-fiber carbon-ceramic composite material brake disc and a preparation method thereof, and belongs to the field of brake discs. The short-fiber carbon-ceramic composite material brake disc is prepared from the following raw materials in percentage by weight: 45-70% of modified short carbon fibers, 1-5% of boron carbide, 3-10% of an adhesive, 2-8% of kaolin, 2-5% of boron nitride, 2-5% of aluminum nitride, 2-6% of carbon black, 2-6% of graphite, 1-5% of a modified dispersant, 1-3% of sodium carboxymethyl cellulose, 1-3% of ethanolamine, 1-4% of sucrose fatty acid ester, 2-6% of nitrile rubber powder and 8-20% of an organic solvent. According to the short-fiber carbon-ceramic composite material brake disc and the preparation method thereof, the high temperature resistance and thermal shock resistance of the carbon-ceramic brake disc can be further improved while the manufacturing period is shortened, the production efficiency is improved and the production cost is reduced, the wear-resistant consistency of the carbon-ceramic brake disc is improved, and the effective service life of the carbon-ceramic brake disc is effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of brake materials, and in particular to a short-fiber carbon-ceramic composite brake disc and a preparation method thereof. Background Art

[0002] Gray cast iron is the first material used to manufacture automobile brake discs. It can achieve a balance between excellent properties such as stable friction, low noise, low wear rate and low manufacturing cost. Therefore, it has been the mainstream automobile brake material since the late 19th century. However, gray cast iron material has severe thermal decay, that is, when friction intensifies and leads to higher temperatures, the braking distance increases and the braking performance decreases.

[0003] Compared with gray cast iron, carbon ceramic brake discs have less thermal decay, lighter weight, shorter braking distance, less braking noise, longer service life and better corrosion resistance. It can be said that carbon ceramic brakes completely crush gray cast iron brake discs in terms of performance and are the upgrade direction of automotive brake materials.

[0004] The disadvantages of carbon ceramic brake discs are that they have a long manufacturing cycle and high cost, and thus the selling price is much higher than that of gray cast iron brake discs. Specifically, in the existing manufacturing process of carbon ceramic brake discs, the raw materials of the brake discs need to be placed in a high temperature and high pressure environment for a long time of die casting, and then undergo a sintering process of about 30 hours to obtain carbon ceramic brake discs; in this preparation process, the manufacturing cycle is long, the production efficiency is low, and the production cost is high. In order to improve production efficiency and shorten the production cycle, if the aforementioned pressing and sintering time is shortened, it will directly lead to a decrease in the physical properties of the brake disc such as hardness, and a shortened effective service life.

[0005] Furthermore, existing carbon-ceramic brake discs have problems such as poor high temperature resistance, poor thermal shock resistance, and poor wear resistance consistency, which directly restrict further improvement of the effective service life of carbon-ceramic brake discs.

[0006] Therefore, the aforementioned technical defects in the existing technology are an important reason that restricts the expansion of carbon ceramic brakes. In the future, as the production technology continues to break through and the product penetration rate increases, the scale benefits will emerge, and the comprehensive performance and production cost of carbon ceramic brakes are expected to be further optimized. If the production cost of carbon ceramic brake discs is significantly reduced, their application can be further penetrated from high-end cars to mid-range cars, and the demand for carbon ceramic brake discs will inevitably increase greatly, with huge substitution advantages and potential. Summary of the invention

[0007] In order to solve the technical problems existing in the prior art, the present invention provides a short-fiber carbon-ceramic composite brake disc and a preparation method thereof, which can shorten the manufacturing cycle, improve production efficiency, and reduce production costs, while further improving the high temperature resistance and thermal shock resistance of the carbon-ceramic brake disc, and improve the wear resistance consistency of the carbon-ceramic brake disc, thereby effectively increasing the effective service life of the carbon-ceramic brake disc.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a short-fiber carbon-ceramic composite brake disc. The raw materials of the short-fiber carbon-ceramic composite brake disc, measured by weight percentage, include: 45-70% modified short-cut carbon fiber, 1-5% boron carbide, 3-10% adhesive, 2-8% kaolin, 2-5% boron nitride, 2-5% aluminum nitride, 2-6% carbon black, 2-6% graphite, 1-5% modified dispersant, 1-3% sodium carboxymethyl cellulose, 1-3% ethanolamine, 1-4% sucrose fatty acid ester, 2-6% nitrile rubber powder, and 8-20% organic solvent; the sum of the weight percentages of the aforementioned components is 100%.

[0009] Preferably, the average particle size of the graphite is 1-100 nm, the average particle size of the carbon black is 1-100 nm, the average particle size of the boron nitride is 500-800 nm, and the average particle size of the aluminum nitride is 2-20 μm; The adhesive is at least one of the following: epoxy resin, methyl cellulose, polyvinyl chloride resin, phenolic resin, bismaleimide BMI, unsaturated polyester resin; The organic solvent is at least one of the following: ethanol, tetrahydrofuran, styrene, perchloroethylene, and a mixture of one or more of ethylene glycol ethers.

[0010] The raw materials are mixed, pretreated, warm-pressed, debinded and sintered to obtain a short-fiber carbon-ceramic composite brake disc.

[0011] The preparation method of the modified chopped carbon fiber comprises the following steps: heat-treating the chopped carbon fiber in an argon atmosphere at 1200-1800° C. for 1.5-2 hours to remove metal ions and impurities on the surface of the chopped carbon fiber; then putting the chopped carbon fiber into acetone, ultrasonically cleaning it until there is no glue on the surface, placing it in an oven after cleaning, and drying it until the acetone is completely volatilized; then immersing the treated chopped carbon fiber in a modification liquid, soaking it at 20-38° C. for 10-25 hours, washing it with distilled water, and then drying it to obtain the modified chopped carbon fiber.

[0012] Preferably, the chopped carbon fibers have a diameter of 6-20 μm and a length of 2-20 mm.

[0013] Furthermore, the modification liquid is an ethanol solution of octadecyl magnesium chloride; the mass percentage content of octadecyl magnesium chloride in the modification liquid is 2.5-3%, and the volume concentration of the ethanol solution is 70-75%.

[0014] The preparation method of the modified dispersant is as follows: according to the mass ratio of boron nitride, graphite, sodium hyposulfite, N-(hydroxymethyl) acrylamide, diethylenetriamine, lauryl acrylate and deionized water being 12-35:15-30:3-5:3-8:2-5:1-2:25-55, the aforementioned materials are mixed evenly and then allowed to stand for 1-3 hours to obtain a mixture; the mixture is placed in a vacuum homogenizer, and vacuum homogenized for 0.5-1 hour under the conditions of a vacuum degree of 0.01-0.06Mpa and a rotation speed of 3000-4300rpm; after the vacuum homogenization is completed, the mixture is placed in a temperature environment of 95-100°C, and dried for 10-50 minutes to remove part of the water, so as to obtain a modified dispersant in a slurry state.

[0015] Furthermore, the method for preparing the short-fiber carbon-ceramic composite brake disc includes the following steps: mixing, pretreatment, warm pressing, debinding, sintering, finishing, weight removal and assembly, and non-destructive testing.

[0016] The mixing method is as follows: according to the aforementioned weight percentages, short-cut carbon fiber, boron carbide, adhesive, kaolin, boron nitride, aluminum nitride, carbon black, graphite, modified dispersant, sodium carboxymethyl cellulose, ethanolamine, sucrose fatty acid ester, nitrile rubber powder, and organic solvent are put into a mixer, the stirring speed is controlled to be 900-1300 rpm, and the mixture is obtained after stirring and mixing for 2-5 hours.

[0017] The pretreatment method is to place the mixture obtained by mixing in a vacuum mud refiner, control the mud refining speed to 32rpm, and perform mud refining for 40-70min, then the mud refining is completed to obtain mud material.

[0018] The warm pressing method comprises placing the pretreated mud material in a warm pressing molding machine, controlling the warm pressing molding temperature to be 50-150° C., the warm pressing molding pressure to be 10-30 MPa, and the warm pressing molding time to be 10-90 min, and obtaining a brake disc green body after molding.

[0019] The debinding method comprises placing the brake disc green body in a vacuum environment, heating it to 700-1200° C. under nitrogen protection, maintaining the temperature for debinding for 80-360 minutes, and cooling it to room temperature after debinding to obtain a porous brake disc green body.

[0020] The sintering method is as follows: placing the porous brake disc blank after debinding in a vacuum environment with a vacuum degree of 10-30Pa, adding silicon powder into the middle crucible where the porous brake disc blank is located, and then introducing nitrogen as a protective gas, first controlling the nitrogen pressure to 0.5-0.6MPa, heating to 300-320°C at a heating rate of 7-9°C / min; then adjusting the heating rate to 4.5-6.5°C / min, heating to 1320-1450°C, and keeping the temperature for 20-40min; then adjusting the heating rate to 3-3.5°C / min, heating to 1700-2100°C, and keeping the temperature for 65-130min; during the insulation process at 1530-2100°C, using a suction device to suck the molten silicon powder into the brake disc; after the insulation is completed, naturally cooling to room temperature to obtain a brake disc preform.

[0021] Preferably, the added weight of silicon powder is 1-7% of the weight of the porous brake disc blank.

[0022] The finishing method is to grind the sintered brake disc preform using a surface grinder and a cylindrical grinder according to the processing requirements of the drawing to obtain a finished brake disc preform.

[0023] The de-weighting assembly method comprises cleaning the powder and dust deposits in the grooves and pores of the finely machined brake disc preform, assembling the preform according to the requirements of the drawing, and obtaining a short-fiber carbon-ceramic composite material brake disc to be inspected.

[0024] The non-destructive testing method is to use an ultrasonic flaw detector to conduct a finished product qualification test on the short-fiber carbon-ceramic composite brake disc to be inspected, and judge the test result by the waveforms of longitudinal waves, transverse waves, surface waves, and plate waves. If the test is qualified, the short-fiber carbon-ceramic composite brake disc is obtained.

[0025] A short fiber carbon-ceramic composite brake disc is prepared by the above-mentioned preparation method.

[0026] Compared with the prior art, the present invention has the following beneficial effects: (1) The short-fiber carbon-ceramic composite brake disc of the present invention has the advantages of short braking distance, light weight, low braking noise, etc. Installing carbon-ceramic brakes is equivalent to reducing weight below the suspension system, which can make the steering wheel more flexible, reduce body vibration, and increase comfort. The excellent performance of carbon-ceramic brakes can match the high requirements of C-class cars and the car modification market for vehicle performance; and if a car is equipped with two pairs of carbon-ceramic brake discs, the fuel consumption per 100 kilometers can be reduced by 0.6-1.2L. For electric vehicles, the cruising range can be increased by 50km. Carbon-ceramic brakes are relatively ideal brake materials for wire-controlled brake systems.

[0027] (2) The method for preparing the short-fiber carbon-ceramic composite brake disc of the present invention adopts carbon-ceramic composite materials. Based on the advantages of low density, high strength, high thermal conductivity, good friction performance and light thermal decay of carbon-carbon composite materials, it can effectively overcome the problem of large attenuation of wet friction coefficient and further optimize the comprehensive performance of the brake disc. It is a new generation of brake material.

[0028] (3) The preparation method of the short-fiber carbon-ceramic composite brake disc of the present invention adopts modified short-cut carbon fiber and other raw materials to effectively shorten the production preparation cycle. At the same time, it cooperates with the warm pressing molding-sintering process to effectively improve the raw material utilization rate and reduce the overall production cost. The production process is simple and stable, and can effectively realize large-scale continuous production.

[0029] (4) The method for preparing the short-fiber carbon-ceramic composite brake disc of the present invention effectively improves the bonding performance between the short-fiber carbon-ceramic composite material and other raw materials, and optimizes the dispersion performance of the short-fiber carbon-ceramic composite material by adopting the modified short-fiber cellulose prepared by a specific method, the modified dispersant and other raw materials in specific amounts; in the subsequent reaction sintering process, the presence of the short-fiber carbon fibers in the carbon-ceramic composite material can introduce a certain amount of microcracks and pore structures into the brake disc matrix, and the microcrack structure can effectively disperse and consume the thermoelastic strain energy of the brake disc when it is subjected to thermal shock, and the presence of the pore structure is beneficial to the relaxation of the brake disc stress, thereby effectively improving the thermal shock resistance of the brake disc; at the same time, it can also effectively improve the wear resistance consistency of the carbon-ceramic composite brake disc and improve the wear resistance of the brake disc.

[0030] (5) The method for preparing the short-fiber carbon-ceramic composite brake disc of the present invention, by adopting modified short-cut cellulose prepared by a specific method, a modified dispersant and other specific amounts of raw materials, can shorten the manufacturing cycle, improve production efficiency, and reduce production costs. At the same time, it can further improve the high temperature resistance and thermal shock resistance of the carbon-ceramic brake disc, and improve the wear resistance consistency of the carbon-ceramic brake disc, thereby effectively extending the effective service life of the carbon-ceramic brake disc.

[0031] (6) The short fiber carbon ceramic composite brake disc of the present invention has a volume density of 2.9 g / cm³ or above, a bending strength of up to 410 MPa, a friction coefficient of 0.3-0.4, and a wear rate reduced to 0.3×10 -7 cm³ / (N·m), and can withstand a maximum temperature of 1910°C; it also has high wear resistance consistency and a long effective service life. DETAILED DESCRIPTION

[0032] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0033] Example 1 The present embodiment provides a method for preparing a short-fiber carbon-ceramic composite brake disc. The raw materials of the short-fiber carbon-ceramic composite brake disc, by weight percentage, include: 45% modified short-cut carbon fiber, 1% boron carbide, 5% adhesive, 2% kaolin, 3% boron nitride, 2% aluminum nitride, 4% carbon black, 4% graphite, 1% modified dispersant, 2% sodium carboxymethyl cellulose, 3% ethanolamine, 2% sucrose fatty acid ester, 6% nitrile rubber powder, and 20% organic solvent; the sum of the weight percentages of the aforementioned components is 100%.

[0034] The average particle size of the graphite is 50 nm, the average particle size of the carbon black is 50 nm, the average particle size of the boron nitride is 600 nm, and the average particle size of the aluminum nitride is 10 μm.

[0035] The binder is methyl cellulose.

[0036] The organic solvent is tetrahydrofuran.

[0037] The preparation method of the modified chopped carbon fiber comprises the following steps: heat-treating the chopped carbon fiber in an argon atmosphere at 1200° C. for 1.5 hours to remove metal ions and impurities on the surface of the chopped carbon fiber; then putting the chopped carbon fiber into acetone, ultrasonically cleaning the chopped carbon fiber until there is no glue on the surface, placing the chopped carbon fiber in an oven after cleaning, and drying the acetone until the acetone is completely volatilized; then immersing the treated chopped carbon fiber in a modification liquid, soaking the chopped carbon fiber at 30° C. for 10 hours, washing the chopped carbon fiber with distilled water, and drying the chopped carbon fiber to obtain the modified chopped carbon fiber.

[0038] The chopped carbon fiber has a diameter of 10 μm and a length of 12 mm.

[0039] The modification liquid is an ethanol solution of octadecyl magnesium chloride; the mass percentage content of octadecyl magnesium chloride in the modification liquid is 2.5%, and the volume concentration of the ethanol solution is 70%.

[0040] The preparation method of the modified dispersant is as follows: according to the mass ratio of boron nitride, graphite, sodium hyposulfite, N-(hydroxymethyl) acrylamide, diethylenetriamine, lauryl acrylate and deionized water being 20:20:3:3:2:1:51, the aforementioned materials are mixed evenly and then allowed to stand for 1.5 hours to obtain a mixture; the mixture is placed in a vacuum homogenizer, and vacuum homogenized for 0.5 hours under the conditions of a vacuum degree of 0.015Mpa and a rotation speed of 3200rpm; after the vacuum homogenization is completed, the mixture is placed in a temperature environment of 95°C, and dried for 10 minutes to remove part of the water, so as to obtain a modified dispersant in a slurry state.

[0041] The method for preparing the short fiber carbon ceramic composite brake disc specifically comprises the following steps: 1. Mixing According to the aforementioned weight percentages, chopped carbon fiber, boron carbide, adhesive, kaolin, boron nitride, aluminum nitride, carbon black, graphite, modified dispersant, sodium carboxymethyl cellulose, ethanolamine, sucrose fatty acid ester, nitrile rubber powder, and organic solvent were put into a mixer, the stirring speed was controlled to 900 rpm, and after stirring and mixing for 2 hours, a mixture was obtained.

[0042] 2. Preprocessing The mixture obtained by mixing the materials is placed in a vacuum mud refiner, and the mud refining speed is controlled to be 32 rpm. After the mud refining is performed for 40 minutes, the mud refining is completed to obtain mud material.

[0043] 3. Warm pressing The pretreated mud is placed in a warm pressing molding machine, the warm pressing molding temperature is controlled to be 50°C, the warm pressing molding pressure is controlled to be 10MPa, and the warm pressing molding time is controlled to be 20min, and a brake disc green body is obtained after molding.

[0044] 4. Glue removal The brake disc green body was placed in a vacuum environment, heated to 700°C under nitrogen protection, and kept warm for 80 minutes for debinding. After debinding, it was cooled to room temperature to obtain a porous brake disc green body.

[0045] 5. Sintering The porous brake disc blank after debinding is placed in a vacuum environment with a vacuum degree of 10Pa, silicon powder is added to the middle crucible where the porous brake disc blank is located, and then nitrogen is introduced as a protective gas, the nitrogen pressure is first controlled to 0.5MPa, and the temperature is increased to 300°C at a heating rate of 7°C / min; then the heating rate is adjusted to 4.5°C / min, the temperature is increased to 1320°C, and the temperature is kept for 20 minutes; then the heating rate is adjusted to 3°C / min, the temperature is increased to 1530°C, and the temperature is kept for 65 minutes; during the insulation process at 1530°C, a suction device is used to suck the molten silicon powder into the brake disc; after the insulation is completed, the temperature is naturally cooled to room temperature to obtain a brake disc preform.

[0046] The added weight of silicon powder is 2% of the weight of the porous brake disc blank.

[0047] 6. Finishing According to the processing requirements of the drawings, the sintered brake disc preform is ground by a surface grinder and a cylindrical grinder to obtain a finely processed brake disc preform.

[0048] 7. Remove heavy assembly The powder and dust deposits in the grooves and pores of the finely machined brake disc preform are cleaned up, and the preform is assembled according to the requirements of the drawing to obtain a short-fiber carbon-ceramic composite brake disc to be inspected.

[0049] 8. Nondestructive testing An ultrasonic flaw detector is used to carry out finished product qualification test on the short-fiber carbon-ceramic composite brake disc to be inspected. The test results are judged by the waveforms of longitudinal waves, transverse waves, surface waves and plate waves. If the test is qualified, the short-fiber carbon-ceramic composite brake disc is produced.

[0050] This embodiment also provides a short-fiber carbon-ceramic composite brake disc manufactured by the aforementioned method.

[0051] After inspection, the short fiber carbon ceramic composite brake disc of this embodiment has a volume density of 2.9g / cm³, a bending strength of 410MPa, a friction coefficient of 0.31, and a wear rate of 0.3×10 -7 cm³ / (N·m), can withstand high temperature of 1820℃; high wear resistance consistency and long effective service life.

[0052] Furthermore, the short-fiber carbon-ceramic composite brake disc of this embodiment is placed in a calcination furnace, and in an air atmosphere environment, the temperature is increased to 1200°C at a heating rate of 20°C / min. After being kept warm for 10 hours, it is cooled to room temperature at a cooling rate of 10°C / min. After repeating this process 20 times, the bending strength of the short-fiber carbon-ceramic composite brake disc can still reach 391MPa, and its thermal shock resistance is good.

[0053] Example 2 The present embodiment provides a method for preparing a short-fiber carbon-ceramic composite brake disc. The raw materials of the short-fiber carbon-ceramic composite brake disc include, by weight percentage: 50% modified chopped carbon fiber, 2% boron carbide, 7% adhesive, 4% kaolin, 3% boron nitride, 3% aluminum nitride, 3% carbon black, 3% graphite, 2% modified dispersant, 2% sodium carboxymethyl cellulose, 2% ethanolamine, 2% sucrose fatty acid ester, 3% nitrile rubber powder, and 14% organic solvent; the sum of the weight percentages of the aforementioned components is 100%.

[0054] The average particle size of the graphite is 50 nm, the average particle size of the carbon black is 50 nm, the average particle size of the boron nitride is 600 nm, and the average particle size of the aluminum nitride is 10 μm.

[0055] The adhesive is epoxy resin.

[0056] The organic solvent is styrene.

[0057] The preparation method of the modified chopped carbon fiber comprises the following steps: heat-treating the chopped carbon fiber in an argon atmosphere at 1500° C. for 1.8 hours to remove metal ions and impurities on the surface of the chopped carbon fiber; then putting the chopped carbon fiber into acetone, ultrasonically cleaning the chopped carbon fiber until there is no glue on the surface, placing the chopped carbon fiber in an oven after cleaning, and drying the acetone until the acetone is completely volatilized; then immersing the treated chopped carbon fiber in a modification liquid, soaking the chopped carbon fiber at 35° C. for 11 hours, washing the chopped carbon fiber with distilled water, and drying the chopped carbon fiber to obtain the modified chopped carbon fiber.

[0058] The chopped carbon fiber has a diameter of 10 μm and a length of 12 mm.

[0059] The modification liquid is an ethanol solution of octadecyl magnesium chloride; the mass percentage content of octadecyl magnesium chloride in the modification liquid is 2.7%, and the volume concentration of the ethanol solution is 72%.

[0060] The preparation method of the modified dispersant is as follows: according to the mass ratio of boron nitride, graphite, sodium hyposulfite, N-(hydroxymethyl) acrylamide, diethylenetriamine, lauryl acrylate and deionized water being 25:20:3:3:3:1:45, the aforementioned materials are mixed evenly and then allowed to stand for 2 hours to obtain a mixture; the mixture is placed in a vacuum homogenizer, and vacuum homogenized for 0.7 hours under the conditions of a vacuum degree of 0.02Mpa and a rotation speed of 3600rpm; after the vacuum homogenization is completed, the mixture is placed in a temperature environment of 98°C, and dried for 30 minutes to remove part of the water to obtain a modified dispersant in a slurry state.

[0061] The method for preparing the short fiber carbon ceramic composite brake disc specifically comprises the following steps: 1. Mixing According to the aforementioned weight percentages, chopped carbon fiber, boron carbide, adhesive, kaolin, boron nitride, aluminum nitride, carbon black, graphite, modified dispersant, sodium carboxymethyl cellulose, ethanolamine, sucrose fatty acid ester, nitrile rubber powder, and organic solvent were put into a mixer, the stirring speed was controlled to 1000 rpm, and after stirring and mixing for 3 hours, a mixture was obtained.

[0062] 2. Preprocessing The mixture obtained by mixing the materials is placed in a vacuum mud refiner, and the mud refining speed is controlled to be 32 rpm. After the mud refining is performed for 55 minutes, the mud refining is completed to obtain mud material.

[0063] 3. Warm pressing The pretreated mud is placed in a warm pressing molding machine, the warm pressing molding temperature is controlled to be 100°C, the warm pressing molding pressure is controlled to be 15MPa, and the warm pressing molding time is controlled to be 60min, and a brake disc green body is obtained after molding.

[0064] 4. Glue removal The brake disc green body was placed in a vacuum environment, heated to 900°C under nitrogen protection, and kept warm for 130 minutes for debinding. After debinding, it was cooled to room temperature to obtain a porous brake disc green body.

[0065] 5. Sintering The porous brake disc blank after debinding is placed in a vacuum environment with a vacuum degree of 20Pa, silicon powder is added to the middle crucible where the porous brake disc blank is located, and then nitrogen is introduced as a protective gas, the nitrogen pressure is first controlled to 0.55MPa, and the temperature is increased to 310℃ at a heating rate of 8℃ / min; then the heating rate is adjusted to 5℃ / min, the temperature is increased to 1380℃, and the temperature is kept for 30min; then the heating rate is adjusted to 3.3℃ / min, the temperature is increased to 1900℃, and the temperature is kept for 100min; during the insulation process at 1900℃, a suction device is used to suck the molten silicon powder into the brake disc; after the insulation is completed, the temperature is naturally cooled to room temperature to obtain a brake disc preform.

[0066] Among them, the added weight of silicon powder is 4% of the weight of the porous brake disc blank.

[0067] 6. Finishing According to the processing requirements of the drawings, the sintered brake disc preform is ground by a surface grinder and a cylindrical grinder to obtain a finely processed brake disc preform.

[0068] 7. Remove heavy assembly The powder and dust deposits in the grooves and pores of the finely machined brake disc preform are cleaned up, and the preform is assembled according to the requirements of the drawing to obtain a short-fiber carbon-ceramic composite brake disc to be inspected.

[0069] 8. Nondestructive testing An ultrasonic flaw detector is used to carry out finished product qualification test on the short-fiber carbon-ceramic composite brake disc to be inspected. The test results are judged by the waveforms of longitudinal waves, transverse waves, surface waves and plate waves. If the test is qualified, the short-fiber carbon-ceramic composite brake disc is produced.

[0070] This embodiment also provides a short-fiber carbon-ceramic composite brake disc manufactured by the aforementioned method.

[0071] After inspection, the short fiber carbon ceramic composite brake disc of this embodiment has a volume density of 3.0g / cm³, a bending strength of 380MPa, a friction coefficient of 0.30, and a wear rate of 0.35×10 -7 cm³ / (N·m), can withstand high temperature of 1910℃; high wear resistance consistency and long effective service life.

[0072] Furthermore, the short-fiber carbon-ceramic composite brake disc of this embodiment is placed in a calcination furnace, and in an air atmosphere environment, the temperature is increased to 1200°C at a heating rate of 20°C / min. After being kept warm for 10 hours, it is cooled to room temperature at a cooling rate of 10°C / min. After repeating this process 20 times, the bending strength of the short-fiber carbon-ceramic composite brake disc can still reach 366MPa, and its thermal shock resistance is good.

[0073] Example 3 The present embodiment provides a method for preparing a short-fiber carbon-ceramic composite brake disc. The raw materials of the short-fiber carbon-ceramic composite brake disc, by weight percentage, include: 53% modified short-cut carbon fiber, 3% boron carbide, 9% adhesive, 2% kaolin, 2% boron nitride, 2% aluminum nitride, 4% carbon black, 2% graphite, 3% modified dispersant, 1% sodium carboxymethyl cellulose, 2% ethanolamine, 3% sucrose fatty acid ester, 6% nitrile rubber powder, and 8% organic solvent; the sum of the weight percentages of the aforementioned components is 100%.

[0074] The average particle size of the graphite is 50 nm, the average particle size of the carbon black is 50 nm, the average particle size of the boron nitride is 600 nm, and the average particle size of the aluminum nitride is 10 μm.

[0075] The adhesive is phenolic resin.

[0076] The organic solvent is ethanol.

[0077] The preparation method of the modified chopped carbon fiber comprises the following steps: heat-treating the chopped carbon fiber in an argon atmosphere at 1800° C. for 2 hours to remove metal ions and impurities on the surface of the chopped carbon fiber; then putting the chopped carbon fiber into acetone, ultrasonically cleaning the chopped carbon fiber until there is no glue on the surface, placing the chopped carbon fiber in an oven after cleaning, and drying the acetone until the acetone is completely volatilized; then immersing the treated chopped carbon fiber in a modification liquid, soaking the chopped carbon fiber at 38° C. for 15 hours, washing the chopped carbon fiber with distilled water, and drying the chopped carbon fiber to obtain the modified chopped carbon fiber.

[0078] The chopped carbon fiber has a diameter of 10 μm and a length of 12 mm.

[0079] The modification liquid is an ethanol solution of octadecyl magnesium chloride; the mass percentage content of octadecyl magnesium chloride in the modification liquid is 3%, and the volume concentration of the ethanol solution is 75%.

[0080] The preparation method of the modified dispersant is as follows: according to the mass ratio of boron nitride, graphite, sodium hyposulfite, N-(hydroxymethyl) acrylamide, diethylenetriamine, lauryl acrylate and deionized water being 17:19:3:3:3:2:55, the aforementioned materials are mixed evenly and then allowed to stand for 3 hours to obtain a mixture; the mixture is placed in a vacuum homogenizer, and vacuum homogenized for 1 hour under the conditions of a vacuum degree of 0.05 MPa and a rotation speed of 4000 rpm; after the vacuum homogenization is completed, the mixture is placed in a temperature environment of 100° C. and dried for 50 minutes to remove part of the water to obtain a modified dispersant in a slurry state.

[0081] The method for preparing the short fiber carbon ceramic composite brake disc specifically comprises the following steps: 1. Mixing According to the aforementioned weight percentages, chopped carbon fiber, boron carbide, adhesive, kaolin, boron nitride, aluminum nitride, carbon black, graphite, modified dispersant, sodium carboxymethyl cellulose, ethanolamine, sucrose fatty acid ester, nitrile rubber powder, and organic solvent were put into a mixer, the stirring speed was controlled to 1300 rpm, and after stirring and mixing for 4 hours, a mixture was obtained.

[0082] 2. Preprocessing The mixture obtained by mixing the materials is placed in a vacuum mud refiner, and the mud refining speed is controlled to be 32 rpm. After the mud refining is performed for 70 minutes, the mud refining is completed to obtain mud material.

[0083] 3. Warm pressing The pretreated mud is placed in a warm pressing molding machine, the warm pressing molding temperature is controlled to be 150°C, the warm pressing molding pressure is controlled to be 30MPa, and the warm pressing molding time is controlled to be 90min, and a brake disc green body is obtained after molding.

[0084] 4. Glue removal The brake disc green body was placed in a vacuum environment, heated to 1100°C under nitrogen protection, and kept warm for 300 minutes for debinding. After debinding, it was cooled to room temperature to obtain a porous brake disc green body.

[0085] 5. Sintering The porous brake disc blank after debinding is placed in a vacuum environment with a vacuum degree of 20Pa, silicon powder is added to the middle crucible where the porous brake disc blank is located, and then nitrogen is introduced as a protective gas, the nitrogen pressure is first controlled to 0.6MPa, and the temperature is increased to 320℃ at a heating rate of 9℃ / min; then the heating rate is adjusted to 6℃ / min, the temperature is increased to 1450℃, and the temperature is kept for 40min; then the heating rate is adjusted to 3.5℃ / min, the temperature is increased to 2100℃, and the temperature is kept for 120min; during the insulation process at 2100℃, a suction device is used to suck the molten silicon powder into the brake disc; after the insulation is completed, the temperature is naturally cooled to room temperature to obtain a brake disc preform.

[0086] The added weight of silicon powder is 5% of the weight of the porous brake disc blank.

[0087] 6. Finishing According to the processing requirements of the drawings, the sintered brake disc preform is ground by a surface grinder and a cylindrical grinder to obtain a finely processed brake disc preform.

[0088] 7. Remove heavy assembly The powder and dust deposits in the grooves and pores of the finely machined brake disc preform are cleaned up, and the preform is assembled according to the requirements of the drawing to obtain a short-fiber carbon-ceramic composite brake disc to be inspected.

[0089] 8. Nondestructive testing An ultrasonic flaw detector is used to carry out finished product qualification test on the short-fiber carbon-ceramic composite brake disc to be inspected. The test results are judged by the waveforms of longitudinal waves, transverse waves, surface waves and plate waves. If the test is qualified, the short-fiber carbon-ceramic composite brake disc is produced.

[0090] This embodiment also provides a short-fiber carbon-ceramic composite brake disc manufactured by the aforementioned method.

[0091] After inspection, the short fiber carbon ceramic composite brake disc of this embodiment has a volume density of 2.9g / cm³, a bending strength of 409MPa, a friction coefficient of 0.40, and a wear rate of 0.51×10 -7 cm³ / (N·m), can withstand high temperature of 1770℃; high wear resistance consistency and long effective service life.

[0092] Furthermore, the short-fiber carbon-ceramic composite brake disc of this embodiment is placed in a calcination furnace, and in an air atmosphere environment, the temperature is increased to 1200°C at a heating rate of 20°C / min. After being kept warm for 10 hours, it is cooled to room temperature at a cooling rate of 10°C / min. After repeating this process 20 times, the bending strength of the short-fiber carbon-ceramic composite brake disc can still reach 387MPa, and its thermal shock resistance is good.

[0093] Comparative Example 1 Comparative Example 1 adopts the technical scheme of Example 1, except that: 1) in the preparation of modified chopped carbon fiber, the modifying liquid adopts sodium tripolyphosphate solution (mass concentration is 1wt%); 2) in the raw materials used in the brake disc, sodium tripolyphosphate is used instead of the modified dispersant; and the mass percentage of each raw material is adjusted as follows: chopped carbon fiber 52%, boron carbide 3%, methyl cellulose 2%, kaolin 3%, boron nitride 2%, aluminum nitride 3%, carbon black 3%, graphite 4%, sodium tripolyphosphate 2%, sodium carboxymethyl cellulose 1%, ethanolamine 1%, sucrose fatty acid ester 1%, nitrile rubber powder 3%, and tetrahydrofuran 20%.

[0094] The brake disc prepared in this comparative example has a volume density of 2.3 g / cm³, a bending strength of 340 MPa, a friction coefficient of 0.31, and a wear rate of 0.9×10 -7 cm³ / (N·m), heat resistance temperature is 1610℃; wear resistance consistency is poor.

[0095] Furthermore, the brake disc of this comparative example was placed in a calcining furnace, and in an air atmosphere, the temperature was increased to 1200°C at a heating rate of 20°C / min, and after being kept warm for 10 hours, it was cooled to room temperature at a cooling rate of 10°C / min; after repeating this process 20 times, the bending strength of the brake disc was 296MPa.

[0096] It can be seen that after changing the modifying liquid of the chopped carbon fiber and omitting the addition of the modified dispersant, the brake disc prepared in this comparative example shows obvious deterioration in volume density, bending strength, wear rate and thermal shock resistance compared to Example 1, and the wear resistance consistency is reduced, and the effective service life of the brake disc is reduced.

[0097] Comparative Example 2 Comparative Example 2 adopts the technical solution of Example 2, except that the preparation of modified chopped carbon fibers is omitted, and untreated raw chopped carbon fibers are used instead of modified chopped carbon fibers.

[0098] The brake disc prepared in this comparative example has a volume density of 3.0 g / cm³, a bending strength of 380 MPa, a friction coefficient of 0.6, and a wear rate of 0.65×10 -7 cm³ / (N·m), the heat resistance temperature is 1850°C; the wear resistance consistency is significantly reduced compared with Example 2.

[0099] Furthermore, the brake disc of this comparative example was placed in a calcining furnace, and in an air atmosphere, the temperature was raised to 1200°C at a heating rate of 20°C / min, and after being kept warm for 10 hours, it was cooled to room temperature at a cooling rate of 10°C / min; after repeating this process 20 times, the bending strength of the brake disc was 351 MPa.

[0100] It can be seen that after using untreated chopped carbon fiber, the brake disc prepared in this comparative example has a significantly higher friction coefficient, a higher wear rate, and poor wear resistance consistency compared to Example 2, and the effective service life of the brake disc is reduced.

[0101] Unless otherwise specified, all percentages used in the present invention are by mass.

[0102] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a short fiber carbon ceramic composite brake disc, characterized in that: The following raw materials are used for preparation, measured by weight percentage: 45-70% of modified chopped carbon fiber, 1-5% of boron carbide, 3-10% of adhesive, 2-8% of kaolin, 2-5% of boron nitride, 2-5% of aluminum nitride, 2-6% of carbon black, 2-6% of graphite, 1-5% of modified dispersant, 1-3% of sodium carboxymethyl cellulose, 1-3% of ethanolamine, 1-4% of sucrose fatty acid ester, 2-6% of nitrile rubber powder, and 8-20% of organic solvent; The adhesive is at least one of the following: epoxy resin, methyl cellulose, polyvinyl chloride resin, phenolic resin, bismaleimide, unsaturated polyester resin; The raw materials are mixed, pretreated, warm-pressed, debinded and sintered to obtain a short-fiber carbon-ceramic composite brake disc.

2. The method for preparing a short fiber carbon ceramic composite brake disc according to claim 1, characterized in that: The preparation method of the modified chopped carbon fiber is as follows: the chopped carbon fiber is subjected to heat treatment in an argon atmosphere at 1200-1800° C.; the chopped carbon fiber is placed in acetone, ultrasonically cleaned and then dried; the chopped carbon fiber is then immersed in a modification liquid, immersed at 20-38° C. for 10-25 hours, washed with water, and dried to obtain the modified chopped carbon fiber; The modified liquid is an ethanol solution of octadecyl magnesium chloride.

3. The method for preparing a short fiber carbon ceramic composite brake disc according to claim 1, characterized in that: The preparation method of the modified dispersant comprises the following steps: evenly mixing boron nitride, graphite, sodium hyposulfite, N-(hydroxymethyl)acrylamide, diethylenetriamine, lauryl acrylate and deionized water, and then standing to obtain a mixture; after vacuum homogenizing the mixture, placing the mixture in a temperature environment of 95-100° C., and drying for 10-50 minutes to obtain the modified dispersant.

4. The method for preparing a short fiber carbon ceramic composite brake disc according to claim 1, characterized in that: The average particle size of graphite is 1-100nm, the average particle size of carbon black is 1-100nm, the average particle size of boron nitride is 500-800nm, and the average particle size of aluminum nitride is 2-20μm; The organic solvent is at least one of the following: ethanol, tetrahydrofuran, styrene, perchloroethylene, and ethylene glycol ether.

5. The method for preparing a short fiber carbon ceramic composite brake disc according to claim 2, characterized in that: In the preparation of the modified chopped carbon fiber, the heat treatment time is 1.5-2h; The mass percentage content of octadecyl magnesium chloride in the modified solution is 2.5-3%, and the volume concentration of the ethanol solution is 70-75%; The diameter of the chopped carbon fiber is 6-20 μm and the length is 2-20 mm.

6. The method for preparing a short fiber carbon ceramic composite brake disc according to claim 3, characterized in that: In the preparation of the modified dispersant, the mass ratio of boron nitride, graphite, sodium hyposulfite, N-(hydroxymethyl)acrylamide, diethylenetriamine, lauryl acrylate and deionized water is 12-35:15-30:3-5:3-8:2-5:1-2:25-55.

7. The method for preparing a short fiber carbon ceramic composite brake disc according to claim 1, characterized in that: The preparation method comprises the following steps: mixing, pretreatment, warm pressing, debinding, sintering, finishing, weight removal and assembly, and non-destructive testing; The mixing method comprises uniformly mixing chopped carbon fibers, boron carbide, adhesive, kaolin, boron nitride, aluminum nitride, carbon black, graphite, modified dispersant, sodium carboxymethyl cellulose, ethanolamine, sucrose fatty acid ester, nitrile rubber powder, and organic solvent to obtain a mixture; The pretreatment method comprises: performing vacuum mud refining on the mixture obtained by kneading to obtain mud material; The warm-pressing method comprises: performing warm-pressing on the mud obtained by pretreatment to obtain a brake disc green body; The debinding method comprises the following steps: vacuum debinding a brake disc green body to obtain a porous brake disc green body; The porous brake disc blank is subjected to sintering, fine machining, weight removal assembly and non-destructive flaw detection to obtain a short-fiber carbon-ceramic composite material brake disc.

8. The method for preparing a short fiber carbon ceramic composite brake disc according to claim 7, characterized in that: The temperature of the warm pressing molding is 50-150°C, the pressure of the warm pressing molding is 10-30MPa, and the time of the warm pressing molding is 10-90min; The debinding process is to place the brake disc green body in a vacuum environment, raise the temperature to 700-1200° C. under nitrogen protection, keep the temperature to debind for 80-360 minutes, and then cool the green body to obtain a porous brake disc green body.

9. The method for preparing a short fiber carbon ceramic composite brake disc according to claim 7, characterized in that: The sintering method is as follows: placing the porous brake disc blank after debinding in a vacuum environment, adding silicon powder into the middle crucible where the porous brake disc blank is located, then introducing nitrogen as a protective gas, heating the temperature to 300-320°C at a heating rate of 7-9°C / min; then adjusting the heating rate to 4.5-6.5°C / min, heating the temperature to 1320-1450°C, and after heat preservation, adjusting the heating rate to 3-3.5°C / min, heating the temperature to 1700-2100°C, and after heat preservation, obtaining a brake disc preform.

10. A short fiber carbon ceramic composite brake disc, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Modification method of layered silicate mineral, layered silicate mineral and application

    CN121627416A